Bicarbonate Elution of Uranium from Amidoxime‐Based Polymer Adsorbents for Sequestering Uranium from Seawater. Issue 13 (5th May 2017) - Pan, Horng‐Bin; Wai, Chien M.; Kuo, Li‐Jung; Gill, Gary; Tian, Guoxin; Rao, Linfeng; Das, Sadananda; Mayes, Richard T.; Janke, Christopher J.
Abstract: Uranium adsorbed on amidoxime‐based polyethylene fibers in simulated seawater can be quantitatively eluted using 3 M KHCO3 at 40 °C. Thermodynamic calculations are in agreement with the experimental observation that at high bicarbonate concentrations (3 M) uranyl ions bound to amidoxime molecules are converted to uranyl tris‐carbonato complex in the aqueous solution. The elution process is basically the reverse reaction of the uranium adsorption process which occurs at a very low bicarbonate concentration (∼10 −3 M) in seawater. In real seawater experiments, the bicarbonate elution is followed by a NaOH treatment to remove natural organic matter adsorbed on the polymer adsorbent. Using the sequential bicarbonate and NaOH elution, the adsorbent is reusable after rinsing with deionized water and the recycled adsorbent shows no loss of uranium loading capacity based on real seawater experiments. Abstract : The bicarbonate elution method offers an efficient and simple method for recovering uranium from amidoxime‐based adsorbents for sequestering uranium from seawater. The adsorbent is reusable after rinsing with deionized water and the recycled adsorbent shows no loss of uranium loading capacity based on real seawater experiments.